Mobilizing the next generation of media leaders: Social support and social capital building increases job satisfaction and loyalty among early-career employees - Olsen, Katie R.; LaGree, Danielle; Tefertiller, Alec (Taylor & Francis, 2024)
The media industry has been disrupted, challenging how young people interact with others in the workplace and develop their professional networks. This study addressed how media managers can support young workers from a social capital perspective. Concepts in the social capital model of organizational socialization were measured through a survey (N = 136) of media professionals in the first five years of their professional careers. Results revealed that social support within organizations helps young people build social career capital. Social career capital also predicted career adaptability, professional self-efficacy, job satisfaction, and employee loyalty. Managerial and theoretical implications are discussed.
Keywords: early-career professionals; social capital; media managers; career development; organizational socialization; social career capital